2017
DOI: 10.1080/15476286.2016.1274853
|View full text |Cite
|
Sign up to set email alerts
|

Modular arrangement of regulatory RNA elements

Abstract: Due to their simple architecture and control mechanism, regulatory RNA modules are attractive building blocks in synthetic biology. This is especially true for riboswitches, which are natural ligand-binding regulators of gene expression. The discovery of various tandem riboswitches inspired the design of combined RNA modules with activities not yet found in nature. Riboswitches were placed in tandem or in combination with a ribozyme or temperature-responsive RNA thermometer resulting in new functionalities. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Those aptamers in combination with different expression platforms have also presented high variability. Except for the utilization of naturally occurring riboswitches, the in vitro systematic evolution of ligands by exponential enrichment (SELEX) is also used for the identification of aptamers that bind non-natural ligands [ 165 ]. However, the conformational changes that are required to make the aptamer active after ligand binding and the artificial conditions under which the aptamers are selected may hamper their functionality in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those aptamers in combination with different expression platforms have also presented high variability. Except for the utilization of naturally occurring riboswitches, the in vitro systematic evolution of ligands by exponential enrichment (SELEX) is also used for the identification of aptamers that bind non-natural ligands [ 165 ]. However, the conformational changes that are required to make the aptamer active after ligand binding and the artificial conditions under which the aptamers are selected may hamper their functionality in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…By overcoming these barriers, engineered riboswitches managed to halt translation both in a cap- and IRES-dependent manner, as well as by controlling ribosomal shunting and splicing. Further research has also shown that gene expression can be regulated from synthetic riboswitches through RNA self-cleavage, by interfering with the RNAi pathway or by controlling microRNA (miRNA) production [ 164 , 165 , 166 , 167 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since several color variations of light-up RNA aptamers have been reported recently, construction of signaling aptamers, which emit fluorescence at different wavelengths in response to different input target molecules, would enable simultaneous imaging of multiple molecules at the single-cell level. The strategy is applicable for not only optimizing signaling aptamers but also for constructing RNAs with modular function as rational design of their allosterically regulated functions is challenging . In addition, the basic technology used for constructing R-CAMPs is that used for next generation sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Modularity is an essential concept in engineering fields that can be applied to synthetic biology. However, engineered devices may not actually exhibit modular behaviour and often a device's features may change under different conditions (30,39,40). Designing the TSD, we observed an influence of the environment surrounding the aptamer cis -elements on its switching behaviour.…”
Section: Discussionmentioning
confidence: 99%